2020
DOI: 10.1007/s11673-020-09993-8
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Gender Self-Advocacy Gap? An Empiric Investigation Into the Gender Pain Gap

Abstract: There are documented differences in the efficacy of medical treatment for pain for men and women. Women are less likely to have their pain controlled and receive less treatment than men. We are investigating one possible explanation for this gender pain gap: that there is a difference in how women and men report their pain to physicians, and so there is a difference in how physicians understand their pain. This paper describes an exploratory study into gendered attitudes towards reporting uncontrolled pain to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(84 reference statements)
3
3
0
Order By: Relevance
“…Specifically, a recent scoping review identified that the majority of research on gender bias was related to cardiovascular disease and that the focus was on strategies to increase adherence to existing guidelines to standardize healthcare (Alcalde Rubio et al, 2020 ). The women in our study employed multiple approaches in attempting to self-advocate which is in line with findings by Kolmes and Boerstler ( 2020 ). Similarly, Maslen and Lupton ( 2018 ) found that women were resourceful, active, and creative in accessing and using online information to enhance their experiences in clinical consultations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, a recent scoping review identified that the majority of research on gender bias was related to cardiovascular disease and that the focus was on strategies to increase adherence to existing guidelines to standardize healthcare (Alcalde Rubio et al, 2020 ). The women in our study employed multiple approaches in attempting to self-advocate which is in line with findings by Kolmes and Boerstler ( 2020 ). Similarly, Maslen and Lupton ( 2018 ) found that women were resourceful, active, and creative in accessing and using online information to enhance their experiences in clinical consultations.…”
Section: Discussionsupporting
confidence: 90%
“…Research on gender and women’s experiences of self-advocating has been conducted in gynaecological and maternal care (Young et al, 2015 ), and in the management of pain (Kolmes & Boerstler, 2020 ). Disenfranchised populations, including women with uncommon medical conditions, are more vulnerable and may be less represented within the dominant culture or systems, leading to additional challenges attempting to self-advocate.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings corroborate research demonstrating that men engage in corresponding but distinct forms of self‐advocacy behaviors compared to women (Kolmes & Boerstler, 2020; O'Malley et al, 2018). Appreciating these differences can assist healthcare providers in supporting patients based on the value patients place on various aspects of their care.…”
Section: Discussionsupporting
confidence: 89%
“…Gould argues that intellectual disability as grounds for abortion in the United States is often based on exaggerated claims about potential quality-of-life disadvantages. Kolmes and Boerstler (2020) delve into difference in pain management between men and women, and their empirical study involving 982 subjects supported the hypothesis that the gender pain gap, about much has been written, was not due to a failure of selfadvocacy.…”
mentioning
confidence: 80%